PENERAPAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN HASIL BELAJAR PKn DALAM KONSEP MAKNA PERSATUAN DI KELAS V SD NEGERI 1 KOTA TERNATE - Fahruni Hamaya; Rustam Hasyim (PEDAGOGIK, 2021)
This study aims to improve Civics learning outcomes with the time token learning model in Civics subjects, the subject of the meaning of unity and precepts of Pancasila in class V SD Negeri 1 Ternate City, the type of research used is Classroom Action Research (CAR). The stages are: 1) planning, 2) implementation and observation, and 3) reflection. The research subjects were 28 students. The object of this research is the time token learning model. The data collection technique in this study was using observation sheets, tests and instrument documentation used to determine student learning outcomes in the form of a multiple-choice test (PG) as many as 10 numbers. The data analysis technique used is descriptive qualitative that is seen from several percent of the success rate of student learning outcomes. Based on the results of the research that has been carried out, it can be concluded that the application of the time token learning model can improve Civics learning outcomes specifically for the meaning of unity and Pancasila precepts in class V SD Negeri I Ternate City. This shows that the students' completeness in the first cycle was 5 students from 28 students who took part in the learning process in the classroom with an average number of 4.29% in the first cycle. While the second cycle of learning student learning outcomes an increase. Of the 28 students who took part in the learning process in the classroom, 24 students who completed the class with an average score of 32.71%. Or in the good category descriptive scale.